2011
DOI: 10.1007/s00442-011-1939-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulses of movement across the sea ice: population connectivity and temporal genetic structure in the arctic fox

Abstract: Lemmings are involved in several important functions in the Arctic ecosystem. The Arctic fox (Vulpes lagopus) can be divided into two discrete ecotypes: "lemming foxes" and "coastal foxes". Crashes in lemming abundance can result in pulses of "lemming fox" movement across the Arctic sea ice and immigration into coastal habitats in search for food. These pulses can influence the genetic structure of the receiving population. We have tested the impact of immigration on the genetic structure of the "coastal fox" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 65 publications
1
57
0
Order By: Relevance
“…These are significantly longer intervals than those observed in both North America and Svalbard where cyclicity of 3-5 years has been reported (Tabel et al 1974;Nadin-Davis et al 2008) but comparable with the 6-10 years suggested by Mørk and Prestrud (2004) for arctic populations in general. The link between the cyclic occurrence of rabies outbreaks in Arctic fox populations reported here and in related studies is often reported as being correlated to fox population density, relying in part on cyclic variations in prey abundance, e.g., rodents (Ballard et al 2001;Dalén et al 2005;Norén et al 2011b). When Arctic fox populations peak in numbers, the likelihood of encounters between individuals increases once the foxes disperse (Tabel et al 1974;Mørk and Prestrud 2004;Mørk et al 2011).…”
Section: Discussionmentioning
confidence: 82%
“…These are significantly longer intervals than those observed in both North America and Svalbard where cyclicity of 3-5 years has been reported (Tabel et al 1974;Nadin-Davis et al 2008) but comparable with the 6-10 years suggested by Mørk and Prestrud (2004) for arctic populations in general. The link between the cyclic occurrence of rabies outbreaks in Arctic fox populations reported here and in related studies is often reported as being correlated to fox population density, relying in part on cyclic variations in prey abundance, e.g., rodents (Ballard et al 2001;Dalén et al 2005;Norén et al 2011b). When Arctic fox populations peak in numbers, the likelihood of encounters between individuals increases once the foxes disperse (Tabel et al 1974;Mørk and Prestrud 2004;Mørk et al 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Immigration might also have contributed somewhat to the observed linkage disequilibrium. Indeed, Noren et al (2011) recently presented genetic evidence for immigration into the Svalbard population following a lemming population crash, and they identified two individuals as likely originating from Siberia.…”
Section: Discussionmentioning
confidence: 99%
“…Its loss and thinning could impede movement and induce a cascade of unprecedented effects [6]. For Arctic fox (Vulpes lagopus), ice allows for long-distance movements, giving rise to a genetically homogeneous population that spans the North American and Svalbard archipelagos [8]. For wolves (Canis lupus), it mediates movement among islands and the mainland, allowing for recolonization of extirpated populations [9].…”
Section: Introductionmentioning
confidence: 99%